COMPARATIVE ANALYSIS OF LOCAL FRUIT SELLING BUSINESSES IN THE SAENAM VILLAGE AND SALLU VILLAGE NORTH CENTRAL TIMOR - Werenfridus Taena; Achmad Subchiandi Maulana; Boanerges P Sipayung; Umbu Joka (Agric, 2022)
East Nusa Tenggara Province has land that tends to be dry, with several superior local fruit commodities such as oranges, mangoes, avocados, and jackfruit. One of the local fruit-producing centers in East Nusa Tenggara is North Central Timor (TTU) Regency. Most of the fruit needs in TTU Regency are supplied from West Miomaffo District, especially Saenam Village. Saenam Village produces 222 Kg of local fruit while Sallu Village is 345 Kg, but the sales volume value of Saenam Village is higher than Sallu Village with a difference of Rp. 1,000,000. Based on these conditions, this study focuses on the comparison of local fruit farming businesses in Saenam Village and Sallu Village. The purpose of this study is to compare and analyze the sales volume, relative market share level, and business position of local fruit commodities by applying BCG analysis. The results showed that the fruit business in Saenam Village had a total sales volume in 2018 of IDR 2,151,313, 2019 of IDR 1,915,296, and 2020 of IDR 2,175,685. Meanwhile, Sallu Village has a total sales in 2018 of Rp 1,009,821, 2019 Rp 899,584, and 2020 Rp 887,281. The market growth rate and relative market share are calculated based on the total sales volume. The results of the BCG analysis show that Saenam Village is in the star quadrant, with a market growth rate of 1.31% and a relative market share level of 2.57. Sallu Village has a market growth rate of -15.25% and a relative market share rate of 0.4. This value explains that the fruit products of Sallu Village are in the dog quadrant. The strategy that needs to be carried out by farmers in Saenam Village is to expand fruit marketing. The strategy that can be applied by farmers in Sallu Village is to replace fruit gardens with vegetable gardens in order to increase income and use land more optimally.